Project Based Learning Using Etno-Stem Approach: Improving Creative Thinking Skill of Pharmacy Students at Medical Vocational High School - Rinto Rinto; R. S. Iswari; B. N. Mindyarto; S. Saptono (International Conference on Science, Education, and Technology, 2022)
This study aims to determine the application of PBL learning with an Ethno-STEM approach and to increase the creative thinking skills of health vocational students in Cirebon. The method used in this research is pre-experimental method and descriptive method. The research sample used in this study was one class from five existing classes, namely class X pharmacy with a total of 35 students by purposive sampling. This study uses observation techniques, written tests, questionnaires, and documentation for collecting data. The data analysis technique used the classical assumption test including the normality test, homogeneity test, and the Normalized Gain (N-gain) test. The results showed that the highest pre-test score was 32.18 and the lowest score was 10.11 with an average value of 21.19. Meanwhile, the post test results obtained the highest score of 95.23 and the lowest score of 49.13. This means that there is an increase in creative thinking skills after the learning. The value of the N-gain of first improvement is in flexible thinking skills which is 70.95% in the medium category, the second improvement is the ability to think fluently with an N-gain of 69.65% in the medium category. The third improvement is original thinking skills with an N-gain value of 69.50 in the medium category. The fourth improvement is the skill of thinking in detail (elaboration) with an N-gain value of 67.37 in the medium category. Finally, the increase in evaluation thinking skills gets an N-gain value of 59.20 in the medium category. Based on the results of the study, it can be concluded that the PBL learning model with the ETNO-STEM approach improves students' creative thinking skills.